International environmental NGOs and the politics of genetically modified organisms: Rethinking resistance in international business. Issue 1 (6th March 2017) - Reis, Yuna; Guedes, Ana Lucia
Abstract : Purpose: The purpose of the paper is to problematize the resistance role played by international environmental non-governmental organizations (IENGOs) in the governance debate over genetically modified organisms (GMOs) to sustain that some of them are important actors in global environmental governance due to their resistance to transnational corporations. Design/methodology/approach: The paper presents a reflection on the literature review focused on civil society and IENGOs. Accordingly, the political role of IENGOs in GMO governance is highlighted grounded on the negotiation process of the Cartagena Protocol. At the end, the authors stress that some IENGOs act as resistance actors to corporations' practices. Findings: The investigation of the political role played by the IENGOs in the negotiation process of the Cartagena Protocol highlighted that these actors use information to influence decision-makers and power holders, often providing know-how and material resources to local activists and social movement organizations at the domestic level. As a result, the political role played by IENGOs in GMO governance places these international actors as highly influential on the international business (IB) domain. Originality/value: This paper highlights the importance of IENGOs as resistant actors in what regards corporations' practices. The authors also sustain that the relationships between states, corporations and civil society actors at the governance level should be part of IB's research agenda to advance the understanding of how civil society mobilizes, articulates and produces consent and coercion in the international domain. Therefore, the paper contributes to foster actors and voices from the margins as a relevant IB research topic.